Proposição de um modelo para análise de viabilidade e seleção de projetos em empreendimentos coletivos agroindustriais - Perressim, William Sbrama (Universidade Federal de São Carlos, 2020)
In several regions of the world, collective agroindustrial projects are important initiatives for the reduction of poverty and hunger. However, they are exposed to a set of particularities that make it difficult and set challenges to success in their implementation. These characteristics require the use of feasibility analysis tools that can incorporate such particularities. Aiming to contribute to the resolution of this problem, this research has as main objective the construction of a model to support decision making, which incorporates the conditions and determinants that affect the performance and viability of the collective agroindustrial projects of industrialization and commercialization in Brazil. A systematic literature review was carried out to identify the performance constraints of collective agroindustrial projects. The proposed model was structured via Simple Multi-Attribute Rating Technique (SMART) modeling, aiming at weighting weights for the factors and determinants from a panel with twenty interviews with experts. The developed model was applied to a portfolio with six collective agroindustrial projects. This application aimed to measure the impact of each determinant in the evaluation of the projects, build the proposed index in real situations and evaluate the results of the implementation of the projects using the proposed analytical tool. The results achieved include the development, proposal and testing of a Project Success Probability Index - IPSP for the analyzed initiatives. The proposed analytical method, with emphasis on the IPSP, proved to be efficient in identifying the most important factors for the success of collective agroindustrial projects.
Proposition of a model for feasibility analysis and project selection in collective agroindustrial enterprises
Keywords: Projetos agroindustriais; Desempenho; Avaliação de projetos; Ações coletivas; Organizações rurais; Agroindustrial projects; Performance; Project evaluation; Farmers’ organization; Collective actions; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::AVALIACAO DE PROJETOS; ENGENHARIAS::ENGENHARIA DE PRODUCAO